Isaac Asimov - Touponce, William F. (Boston : Twayne Publishers, 1991)
Examines each of Asimov's major works of science fiction in terms of its chronological setting within the Asimovian universe.
Includes bibliographical references (p. 110-118) and index.
School Library Journal.
Young Adult.
Young Adult
Keywords: Asimov, Isaac, -- 1920-1992 -- Criticism and interpretation; Asimov, Isaac, -- 1920-1992.; Science fiction, American -- History and criticism; Science fiction -- History and criticism